Congenital myotonic dystrophy: respiratory function at birth determines survival. Issue 2 (February 1989) - Rutherford, M A; Heckmatt, J Z; Dubowitz, V
Abstract : The clinical features of 14 neonates with congenital myotonic dystrophy were retrospectively reviewed. These babies represent all the new cases of congenital myotonic dystrophy seen in this department since 1982. Twelve babies were referred because of either difficulties in diagnosis or difficulties in the management of their respiratory problems. Of the 14 babies, 13 had birth asphyxia, 11 were premature, and four had intrauterine growth retardation. Ten babies required artificial ventilation from birth. Abnormalities on chest radiography included thin ribs (n =9) and raised right hemidiaphragms (n = 5). Recurrent episodes of collapse and consolidation of the lungs secondary to poor swallowing occurred in all ventilated babies. All babies ventilated for longer than four weeks died of respiratory complications before the age of 15 months. One baby was successfully extubated after diaphragmatic plication, but he died a few months later. Duration of ventilation was the best guide to prognosis.